HUBUNGAN FAKTOR KEPRIBADIAN DAN STRATEGI PEMBELAJARAN BAHASA DALAM MENGEMBANGKAN KETERAMPILAN BERBICARA - Asrawaty, Andi; Mas'ud, Bulqia; Imansari, Nurul (BASIS (Bahasa dan Sastra Inggris), 2022)
Speaking skill was one of essential parts in language learning and needed to be mastered by every student for a better foreign language communication. The aims of this research were (1) to find out the language learning strategies used by the students based on their personality factors (2) to observe the extent to which the personality factors and language learning strategies correlate with speaking skill, (3) to elaborate the interplay of personality factors and language learning strategies in developing students’ speaking skill. 25 students in the fourth semester of 2015/2016 class of English Education Department at Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Muhammadiyah Bone were selected by purposive sampling. The research employed mixed method of descriptive quantitative (correlation) and descriptive qualitative analysis. Quantitative data were collected first from questionnaires and speaking test and qualitative data from interview. The results of the research indicated that most of extrovert students prefer to use indirect learning strategies (69%) while introvert students prefer to use direct learning strategies (89%). The correlation of personality factors and speaking skills was low (r=0.08), whereas the correlation of language learning strategies and speaking skill was strong (r=0.6). Therefore, the interplay of personality factors and language learning strategies showed that personality factors contribute to important roles in choosing the appropriate language learning strategies in developing speaking skill.